Study of Weed Communities in Immature and Producing Plant Stages of Clove Crops in Ariate Village, West Seram Regency - Johan Riry; Vilma Laurien Tanasale; Joel Kermite (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2024)
This research was conducted in the clove plantation area in Ariate Village, Huamual District, West Seram Regency. The research took place from September 12 to October 12, 2020, with the aim of identifying weed communities in the immature and productive stages of clove plants. This study used the weed survey method to collect data by direct survey in the field. In conducting vegetation analysis, the purposive quadrat method was used, with primary data consisting of weed species and populations, density and biomass (dry weight) in the clove plantation area, the observed block area measuring 1 x 1 m with a total of 10 plots . As for secondary data in the form of general data of the region (general condition of the location) and climatic data for the last 5 years, as a comparison material, in the form of parameters measured directly in the field such as soil pH, soil moisture, and temperature, at the TBM and TM stages. The results of the study found that in the clove planting area in Ariate Village, 25 types of weeds were found in the immature plant stage and 27 types of weeds in the mature plant stage and Clidemia hirta weed was the dominant weed in both plant stages so that weed control advice at both different plant stages is the same, namely by using integrated control.